THE ROLE OF ELDERLY FAMILY DYNAMICS IN MANAGING CLINICAL DEPRESSION: INSIGHTS FROM THERAPY - Thika Marliana; Iis Indriayani; Agung Tri Nugraha; Jamiatun Jamiatun (Yayasan Adra Karima Hubbi, 2026)
Late-life clinical depression is influenced not only by psychological factors but also by family dynamics that shape treatment adherence and emotional recovery. However, the role of family involvement in geriatric depression management remains insufficiently explored. This qualitative phenomenological study involved 20 older adults diagnosed with clinical depression and 20 family members participating in therapeutic care. Participants were recruited from the teman curhat.ID telecounseling service. Data were collected through semi-structured interviews and analyzed using thematic analysis with independent coding and constant comparative techniques. Three major themes emerged: navigating the burden of care, communication dynamics as a therapeutic catalyst, and structural intersections of professional and familial care. Supportive family communication, emotional validation, and collaborative caregiving improved treatment adherence, emotional resilience, and recovery outcomes. Conversely, caregiver burden, unresolved conflict, and excessive familial control reduced patient autonomy and hindered emotional independence. Balanced family-centered interventions are essential to strengthen therapeutic effectiveness while preserving psychological autonomy in elderly individuals with clinical depression.